Laparoscopic Ladd's procedure in neonates: A simple landmark detorsion technique. Issue 7 (10th June 2020) - Pham, Hien Duy; Okata, Yuichi; Vu, Hoan Manh; Xuan, Nam Tran; Duc, Tam Tran
Abstract: Background: The aim of this study was to assess the efficacy of our simple landmark technique for laparoscopic detorsion and the Ladd's procedure (lap‐Ladd) for malrotation with midgut volvulus in neonates and to identify the risk factors for reoperation after the lap‐Ladd. Methods: We conducted a retrospective chart review of 42 patients after lap‐Ladd for malrotation between April 2017 and June 2019. Information regarding patient status and intraoperative and postoperative data were analyzed. Results: Thirty‐one patients had volvulus (73.8 %), while 11 patients did not (26.2%). The median age and weight between the two groups at operation were 9 days (range, 3–28 days), 3.2 kg (range, 2–8 kg) and 6 days (range, 2–11), 2.9 kg (range, 2–3.8 kg), respectively. The operative time was significantly shorter in patients with volvulus compared to those without (60 vs 105 min, P = 0.002). Two cases were converted to open surgery because of ischemic changes of the total small intestine during surgery. Reoperation was required in two patients with volvulus (due to adhesive small bowel obstruction and recurrent volvulus). There was no significant predictive factor for reoperation after the lap‐Ladd procedure. Conclusion: Our simple landmark lap‐Ladd procedure demonstrated feasibility and good short‐term outcomes in neonates with malrotation, regardless of the presence or absence of volvulus.